2q31.1 microdeletion syndrome: redefining the associated clinical phenotype. Issue 2 (10th November 2010) - Dimitrov, Boyan; Balikova, Irina; de Ravel, Thomy; Van Esch, Hilde; De Smedt, Maryse; Baten, Emiel; Vermeesch, Joris Robert; Bradinova, Irena; Simeonov, Emil; Devriendt, Koen; Fryns, Jean-Pierre; Debeer, Philippe
Abstract : Introduction: The clinical phenotype of the chromosome 2q31 deletion syndrome consists of limb anomalies ranging from monodactylous ectrodactyly, brachydactyly and syndactyly to camptodactyly. Additional internal organ anomalies—for example, heart defects, ocular anomalies—may be present. Hemizygosity for HOXD13 and EVX2 genes was thought to cause the observed skeletal defects. Recently, based on the phenotype of patients with overlapping 2q31 interstitial deletions, a new SHFM5 locus was proposed, proximal to the HOXD cluster, between EVX2 and marker D2S294. DLX1 and DLX2 haploinsufficiency was suggested as the most plausible explanation for the observed SHFM-like limb anomalies in these cases. Methods and results: Five unique, interstitial 2q31 deletion patients were selected to further characterise the 2q31 region and to establish a genotype/phenotype correlation map. The size of the deletions was delineated with a chromosome 2 specific tiling path bacterial artificial chromosome (BAC) array. The clinical and molecular data for this group of patients were compared to others in the literature. A common locus for the observed skeletal anomalies, including the HOXD genes and surrounding regulatory sequences, was delineated. These results correlate with recently published studies in animal models. In addition, a critical region for the facial gestalt of the 2q31.1 microdeletion syndrome was delineated. Conclusions: These results reinforce the hypothesis that the variable skeletal phenotype in 2q31 deletion patients is a result of hemizygosity for the HOXD genes and that the 2q31.1 microdeletion syndrome is a well defined and clinically recognisable phenotype.